Development of a Diagnostic Test Based on Three-Tier Multiple Choice to Identify Student Misconceptions on Circulatory System Material - Nisa, A. Khaeru; Ismail, Ismail; Adnan, Adnan (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
This research is a research and development (R&D) type formative research Tessmer which aims to develop a three-tier multiple choice diagnostic test that can identify student misconceptions on circulatory system material. The product development stage consists of two stages, namely the preliminary stage and formative evaluation (self evaluation, prototyping). The subjects in this study were students of class XI MIPA SMAN 10 Bone. Based on the results of the study, it can be concluded that the final prototype or final product of the three-tier multiple choice diagnostic test instrument developed as a whole is included in good quality in terms of validity, reliability, level of difficulty and differentiation. Based on the results of the analysis, it shows that the three tier multiple choice diagnostic test instrument is successful and effective in identifying student misconceptions on circulatory system material with the percentage of students who experience misconceptions is 38.6%